Correction: Indirect Immunofluorescence Assay for the Simultaneous Detection of Antibodies against Clinically Important Old and New World Hantaviruses. - Sabine Lederer; Erik Lattwein; Merle Hanke; Karen Sonnenberg; Winfried Stoecker; Åke Lundkvist; Antti Vaheri; Olli Vapalahti; Paul K S Chan; Heinz Feldmann; Daryl Dick; Jonas Schmidt-Chanasit; et al. (Public Library of Science (PLoS), 2020)
[This corrects the article DOI: 10.1371/journal.pntd.0002157.].